The present-day landscape of Bukit Keluang formation: geoheritage potential for conservation and geotourism - Muhammad Ashahadi Dzulkafli,; Norasiah Sulaiman,; Azrin Azmi,; Kamal Roslan Mohamed,; Che Aziz Ali, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The Late Permian sedimentary rock of Bukit Keluang Formation is well exposed on three isolated hills namely the Bukit Keluang, Bukit Bubus and Bukit Dendong. The consecutive hills exhibit a unique landscape of linear ridge surrounded by the alluvial plains and are well known for their beautiful sandy beaches and outstanding landscapes. Geological landscape in the area falls into three heritage value set (scientific, aesthetic and recreational value) that in need of immediate conservation. Scientific evidence shows that the study area exhibits a unique lithologically and structurally controlled landscape characterised by first order topography of folded and thrusted sequence (anticlinal hill), linear cuesta ridge and denudation hill. Differential erosion of the conglomerate-sand-shale sequences led to the development of linear ridge with different elevation profiles. The geometric and geographic position of the hills conforms with the regional structural trend in the area with the N-S trending fault system is inferred as the major fault that displaced the Bukit Keluang Formation. Internal complexities in the individual structures in the form of cross-faults, oblique-faults and lineaments trending NW-SE, NE-SW to N-S directions have formed cave morphological feature and divide the hills into separate blocks. The geological landscape also contributes to an aesthetic value such as the beautiful hilly landscape and sandy beach, while recreational values including hiking, mountain biking and water activities. Geological heritage and geotourism could have a positive future in Bukit Keluang, Bukit Bubus and Bukit Dendong. The in-situ and ex-situ geological conservation is urgently needed in order to support the efforts to implement geoscience knowledge to the public.